Improved Knowledge of Equine Parasitic Diseases and Feed Management - Yanti, Yuli; Riyanto, Joko; Cahyadi, Muhammad; Wati, Ari Kusuma; Pawestri, Wari (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to provide outreach through knowledge about feeding management and parasitic diseases in horses. Community service activities by the TAP&D (Tropical Animal Production and Disease) Research Group were held at the Bendi Horse Sukoharjo community group on June 25, 2023, in Sukoharjo Regency, Central Java. Data were collected using interviews and observation. All data obtained were then analyzed descriptively. The horses used are descendants of Banyuwangi horses. This bendi is used by the owner to attract or transport tourists who come to Sukoharjo Square every Monday to Sunday. The horses used are generally small, and some are even skinny. After analyzing horse faeces in the laboratory at the start of the pre-survey, it was found that 100% of the bendi horses in the association were infected with worms. Diseases in horses can also be caused by poor feed management. So, the solution is to provide education on maintaining good horse practices, especially feed management. The next problem is that the feed given to horses usually consists of long grass, so the horse doesn't eat all the parts. The solution we provide is a grass chopper. After the service activities were carried out, farmers increased their knowledge regarding parasitic diseases in horses and good feed management. This service activity concludes that horse farmers have increased knowledge about good horse care and about horse diseases.